2022
DOI: 10.3390/app12199625
|View full text |Cite
|
Sign up to set email alerts
|

Quality Prediction and Parameter Optimisation of Resistance Spot Welding Using Machine Learning

Abstract: In a small sample welding test space, and to achieve online prediction and self-optimisation of process parameters for the resistance welding joint quality of power lithium battery packs, this paper proposes a welding quality prediction model. The model combines a chaos game optimisation algorithm (CGO) with the multi-output least-squares support vector regression machine (MLSSVR), and a multi-objective process parameter optimisation method based on a particle swarm algorithm. First, the MLSSVR model was const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The analysis of the monitoring data showed that the movement of the electrodes reflected thermomechanical phenomena during the process, such as unbalanced spot heating. Following this, a more advanced approach in [67] presents a ML-based quality prediction model for the case of single-sided double-jointed RSW of overlapped Ni-Cu sheets. By using a constant voltage controller and considering the input process parameters as predictors and the nugget diameters and tensile shear load of the joints as targets, the authors developed a multi-output regression model.…”
Section: Resistance Spot Weldingmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the monitoring data showed that the movement of the electrodes reflected thermomechanical phenomena during the process, such as unbalanced spot heating. Following this, a more advanced approach in [67] presents a ML-based quality prediction model for the case of single-sided double-jointed RSW of overlapped Ni-Cu sheets. By using a constant voltage controller and considering the input process parameters as predictors and the nugget diameters and tensile shear load of the joints as targets, the authors developed a multi-output regression model.…”
Section: Resistance Spot Weldingmentioning
confidence: 99%
“…In particular, those that have been found either include process optimisation as a side research task or focus on modelling of some aspects of the process. In [67], as mentioned above, the authors trained a ML model to predict the nugget diameters and the tensile shear loads of the joints. Later, they used this model to identify the optimal process parameters and maximise the tensile shear load of the joints or select the right parameters to achieve a given value.…”
Section: Resistance Spot Weldingmentioning
confidence: 99%
“…Resistance spot welding (RSW), which is categorized as a pressure welding technique, is now the primary assembly process used in the automobile industry and other sectors. For several decades, the aerospace industry has recognized the economic benefits of spot welding [1][2][3][4]. Around 90% of all vehicle body assemblies use resistance spot welds [5].…”
Section: Introductionmentioning
confidence: 99%
“…This manual inspection is too expensive and time consuming. In response to the problems associated with the manual inspection of defects [ 5 ], automatic detection techniques such as pattern recognition and machine learning are mainly used [ 6 , 7 , 8 ]. Machine-vision-based defect detection systems can also be deployed to detect faults in batteries.…”
Section: Introductionmentioning
confidence: 99%